Culm Traits and its Relation with Lodging in Rice (Oryza sativa L.) - Joarder, N; Gupta, UK; Sima, SN (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Culm traits; Lodging index; Regression; Heritability Bangladesh j. genet. biotechnol. 7(1&2): 29-32 2006 (June & December)